The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317717984
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical optical spectroscopy for the early diagnosis of gastrointestinal neoplasms

Abstract: Gastrointestinal cancer is a leading contributor to cancer-related morbidity and mortality worldwide. Early diagnosis currently plays a key role in the prognosis of patients with gastrointestinal cancer. Despite the advances in endoscopy over the last decades, missing lesions, undersampling and incorrect sampling in biopsies, as well as invasion still result in a poor diagnostic rate of early gastrointestinal cancers. Accordingly, there is a pressing need to develop noninvasive methods for the early detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 163 publications
1
16
0
1
Order By: Relevance
“…This is the first time; breast cancer biopsy data was explored using AI and ML approaches based on subtype classification. AI approach studies have identified malignant tissues from normal and benign in various cancers such as lung cancer [54,60], skin cancer [61,62], brain cancer [18,63], gastro intestinal cancer [64,65], and oral cancer [66].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time; breast cancer biopsy data was explored using AI and ML approaches based on subtype classification. AI approach studies have identified malignant tissues from normal and benign in various cancers such as lung cancer [54,60], skin cancer [61,62], brain cancer [18,63], gastro intestinal cancer [64,65], and oral cancer [66].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 It can directly detect tumor tissue samples and quickly determine the internal molecular structure and characteristics of the samples, with the ability to identify subtle molecular changes in biological components even at the initial stage of the lesions. 20 Our team has performed Raman spectroscopy to detect breast cancer microcalcification, thus confirming its diagnostic utility. 13,21,22 Compared with normal tissues, the C-O bond stretching vibration of the b-sheet of amide I band (1610 cm À1 ) in protein appeared in breast AH tissues, indicating that the C-O group in the protein was severely damaged when the breast epithelial cells became cancerous, resulting in destruction of the protein conformation space.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, in the progressive stages of cancer, the epithelial tissue thickness increases, that results in reduced amount of light delivery to the collagen fiber of connective tissue, which ultimately alters the scattering coefficient and the diffuse reflectance spectral intensity. 68 Therefore, DRS is a sensitive tool, enabling diagnosis of cervical cancer, 69 gastrointestinal cancer, 70 skin cancer, 22 colon cancer, 71 breast cancer, 72 brain tumor, 73 lung cancer, 74 and renal carcinoma, 75 because they rely on the tissues biochemical and morphological feature. In the following section, we shortly describe the application of DRS for certain types of cancer diagnosis, without covering all the above-mentioned cancers.…”
Section: Medical Applicationsmentioning
confidence: 99%